BS EN IEC 60318-8. Electroacoustics. Simulators of human head and ear. Part 8. Acoustic coupler for high-frequency measurements of hearing aids and earphones coupled to the ear by means of ear inserts (29th May 2020) - British Standards Institution,
No abstract available